Técnicas de geoprocessamento para o mapeamento de habitats de onça-pintada no Cerrado e Floresta Mato-grossense - Cézar, Adelaine Alves (2011)
The jaguar is the animal with the most expansive habitat demands. Geoprocessing techniques are very important when it comes to analyze the spacial distribution of the Jaguar ( Panthera onca) and related facts, such as the type of land and vegetation use and spalling. The Jaguar’s habitats in the State of Mato Grosso were mapped according the observations made by the Onça Pintada Institute (IOP), which were done from 2004 until 2009. In this observation it was found 236 places in which the Jaguar presence was noticed. With these informations and the adding of pseudoabsence, it was related a total of 15 independent variables, which we can highlight the use and occupation of the land, road infrastruction, hydrography and land relief. The analysis indicated the predominant use, percentage use, route density, edges density and the size of the spots as a predetermine of the species presence/absence. The result of the logistic regression is that the south, southeast and mid north of The State of Mato Grosso are the areas where there‘s no environmental/ecological condition for the species. Those areas are mainly used for big crops and husbandry. In other hand, good conditions were found in special areas, where the maintenance of the species is the priority.